AN ANALYSIS OF STUDENTS PERCEPTION ON DESCRIPTIVE TEXT USING GOOGLE DOCS IN TENTH GRADE STUDENTS of SMK NEGERI 1 JEMBER - RINA DIAH DARAS TIKA; Rita Hartati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
Tika, Rina. 2023. An Analysis of Students Perception on Descriptive Text Using Google Docs in Tenth Grade Students of SMK Negeri 01 Jember in 2022/2023 Academic Year. Thesis, English Language Education Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Jember. Advisors: (1) Fitrotul Mufaridah, M.Pd (2) Nurkamilah, M.PdKeyword: Online Learning, Google Docs, Writing Text, Descriptive TextImplementing online learning tools within EFL contexts will help better address the multitude of teaching and learning styles. Google docs is a free and easy-to-use technology on which individual, pair, and groups of students can create, write, edit, store, comment and give immediate feedback on their writing simultaneously from their computers or other tablet devices they have in and outside the classroom. In this research, the researcher conducted research about perception on the use of Google Docs. The problem of this research is what is students’ perception of writing text online using Google Docs. This research aims to know the strategy use by the students in writing descriptive text online using Google Docs.The researcher will discuss about writing descriptive text using Google Docs. The use of Google Docs is common media used during 2022/2023. Google Docs helps the teacher to deliver the material. In this case, writing tasks require students to produce a shared text. In groups, students scaffold tasks and achieve a more developed product. Google Docs facilitates writing instructional practices. Google Docs allows people to work, read, review, comment, and edit to each other in the same document simultaneously (Deveci, 2018; Ishtaiwa & Aburazeq, 2015). It gives the benefits that Google Docs offers, this research reported sought to explore students’ perception on writing processes using Google Docs, especially in generating their ideas, organizing the text, and constructing the sentences in writing descriptive text.This research used descriptive research because based on the research problem; the objective of this research it is to know students’ perception of writing text online using Google Docs for SMK Negeri 01 Jember in 2022/2023 Academic Year.Based on the data, students' perspective on Google Docs is positive. From the students' view can be seen how Google Docs help students to do assignments anywhere, anytime, can access these tools directly to correct their assignments and submit to the teacher. They also get other positive things when they want to find information of assignment by accessing it on their cellphone while they are working on Google Docs. In other side, they also find difficulty in internet access.